Fine Mapping of a Dravet Syndrome Modifier Locus on Mouse Chromosome 5 and Candidate Gene Analysis by RNA-Seq - Hawkins, Nicole A.; Zachwieja, Nicole J.; Miller, Alison R.; Anderson, Lyndsey L.; Kearney, Jennifer A. (PLOS Genetics, 2016)
Author Summary Epilepsy is a neurological disorder affecting approximately 3 million Americans and 1% of the worldwide population. Approximately 70% of patients diagnosed with epilepsy have a genetic basis for their disease. The same genetic mutation can result in epilepsy with varying clinical severity in some individuals. This suggests that additional factors modify the effect of the primary mutation, resulting in the differences observed. Mouse models of epilepsy also exhibit variable severity depending on the inbred strain background. This is a useful model system that enables us to determine other genetic factors that influence phenotype presentation. This study investigates a mouse model of Dravet syndrome. Similar to Dravet syndrome patients, the mice experience a variety of seizure types and have increased risk for premature death. Interestingly, the Dravet syndrome phenotype is completely masked on one mouse strain background. Through a series of genetic and pharmacological techniques we were able to identify a gene that is likely responsible for the strain-dependent phenotype difference of Dravet mice. Identifying genes that modify diseases can help predict patient outcomes and suggest new therapies for the treatment of epilepsy.